Advanced Ambulatory Operating Stretcher Learned by Means of Convulational Neural Network (CNN) - Talpur, Sariena; Khoso, Nazaruddin (British Journal of Healthcare and Medical Research, 2018)
According to scientists transportation is the major problem in today’s world. The paper presents a method to transferring the patient from long distances or even from shorter distance. Concerned people face many problems in transferring the patient from one place to another place even from ambulance to stretcher or from stretcher to bed and vice versa. Some of the time it is difficult to move the stretcher because of the heavy weight of the patient, It requires more than two or three person in engaging the stretcher while in transferring patient. It will also cause un-peaceful conditions in the hospital and also it will effect on patient’s health too. We tried to overcome these problems via Transfer learning with the help of convolutional neural network in order to move the patients. This type of stretcher solve the problem through self-operating stretcher instead of it operates manually.